Analysis of decadal land cover changes and salinization in Urmia Lake Basin using remote sensing techniques - Alizade Govarchin Ghale, Yusuf; Baykara, Metin; Unal, Alper (Copernicus GmbH, 2017)
Abstract. Urmia Lake located in the north-west of Iran, is one of the largest hyper-saline lakes in the world. In recent years, most of the Urmia Lake have been rendered to unusable lands. Drought and rapid increase in agricultural activities are the most important reasons behind the shrinkage of the Lake. This kind of exploitation with the added salinity from irrigation occurring over time has caused increased soil salinity in the basin leading up to desertification. Soil salinity research are crucial to understand underlying causes and consequences of the drying Urmia Lake. In this study, we use remote sensing technology and image processing techniques to detect spatio-temporal variability of salt body, salt affected lands, and development of irrigated lands to estimate the extend of salinization in terms of spectral response of satellite images for the Urmia Lake Basin from 1975 to 2016. The results of this study indicate that salt and salty soil areas has increased dramatically from 1995 to 2014 and more than 5000 km2 of Urmia Lake's water surface area was converted to salt or salty soil bodies during recent years. Salinization and desertification progress are not limited to just dried bottom of the Urmia Lake. Although the area of irrigated lands has increased more than two times during the studied period, soil salinity has increased in regions close to Urmia Lake too. This desertification in the basin have potential to be the source of dust storms, which have adverse effects on people's life and climate as well.